Courtyard by Marriott Bali Nusa Dua Resort: A Support for Employee Productivity during the Covid-19 Pandemic - Ni Wayan Budi Purnama Dewi; Ni Made Ernawati; I Gede Mudana (Badan Riset dan Inovasi Daerah Provinsi Bali, 2021)
Purpose: This study attempts to describe the efforts made by Courtyard by Marriott Bali Nusa Dua Resort in supporting employee’s productivity during the Covid-19 pandemic. Research method: Data collection techniques are done through interview. Data gained were analyzed in a descriptive-qualitative way. Results and discussion: The efforts made by Courtyard by Marriott Bali Nusa Dua Resort can support the productivity of its employees by conducting online and offline training activities. Analysis of the quantity, quality and work time of employees, show that the training is really carried out. Implication: The training activities implemented by Courtyard by Marriott Bali Nusa Dua Resort have indirectly facilitated employee productivity during the Covid-19 pandemic.